The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3892/etm.2018.6480
|View full text |Cite
|
Sign up to set email alerts
|

Triptolide protects podocytes via autophagy in immunoglobulin A nephropathy

Abstract: Triptolide is often used to treat patients with immunoglobulin A nephropathy (IgAN), especially in Asia. However, its detailed mechanism remains unclear. In vitro experiments were conducted with podocytes exposed to aggregated IgA (aIgA)-MSC1097-conditioned media. A total of four groups were compared in this study: A control group (CON); a healthy supernatant group (HEAs); an IgAN supernatant group (IgANs); and a triptolide group (TRI). First, aggregated IgA1 (aIgA1) was generated by heating monomeric IgA1 (mI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…The autophagy activity of podocytes has a bidirectional change under different injury conditions. For example, in patients with diabetes (Wu et al, 2018;Zhao et al, 2018;Li et al, 2020) and IgA nephropathy (Liang et al, 2018), decreased podocyte autophagy activity is observed; while in systemic lupus erythematosus (SLE) (Jin et al, 2018) or adriamycin-induced models of nephrotic syndrome (Yu et al, 2018), podocyte autophagy activity is found to be increased. Yu et al (2019) observed an increase in the number of autophagosomes and the expression of autophagy-related proteins such as LC3B-II and Beclin-1 in podocytes stimulated by lupus autoantibodies.…”
Section: Discussionmentioning
confidence: 99%
“…The autophagy activity of podocytes has a bidirectional change under different injury conditions. For example, in patients with diabetes (Wu et al, 2018;Zhao et al, 2018;Li et al, 2020) and IgA nephropathy (Liang et al, 2018), decreased podocyte autophagy activity is observed; while in systemic lupus erythematosus (SLE) (Jin et al, 2018) or adriamycin-induced models of nephrotic syndrome (Yu et al, 2018), podocyte autophagy activity is found to be increased. Yu et al (2019) observed an increase in the number of autophagosomes and the expression of autophagy-related proteins such as LC3B-II and Beclin-1 in podocytes stimulated by lupus autoantibodies.…”
Section: Discussionmentioning
confidence: 99%
“…A screening of 102 cytokines using a proteome array was performed to highlight new and interesting pro-inflammatory proteins upregulated in human keratinocytes upon leptin stimulation. We observed that leptin stimulated secretion of several psoriasis-related cytokines, for example CCL20, a CCR6 ligand, strongly chemotactic for lymphocytes and upregulated by IL-17A, IL-22 and TNFα 46 ; IL-6, CXCL-1 and IL-8, pro-inflammatory cytokines increased in psoriatic skin, associated with chemoattraction of lymphocytes and keratinocyte proliferation 33,39,47 ; hBD2, which is overexpressed in psoriatic skin and also induced by TNFα and IFNγ 48,49 but also IL-17A and IL-22 50 and MMP9, a collagenase acting as an angiogenesis promoting factor, which is increased in psoriasis. 51 Induced secretions of IL-6 and IL-8 by leptin have previously been reported 7,29 ; however, induced secretions of CCL20, CXCL1 and MMP9 extend the list of psoriasisrelated proteins stimulated by leptin.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the activation of mTORC1 in podocytes, which results in the inhibition of autophagy, leads to accelerated DN ( 110 ). Furthermore, Liang et al found that TP protects podocyte autophagy by suppressing the mTOR and AKT pathways in IgAN ( 56 ) ( Table 1 , Figures 2 , 3 ).…”
Section: Effects Mechanisms and Therapeutic Targets Of Tp Against Proteinuria And Kidney Injury In Dnmentioning
confidence: 99%